2022
DOI: 10.1097/jom.0000000000002616
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Mental Health Consequences of COVID-19 Pandemic in the Aviation Community in Greece

Abstract: COVID-19 pandemic has posed a major occupational and economical risk to the commercial aviation industry, although risk assessment remains unaccounted for. The described in this paper sleep and mental health disturbances due to the pandemic, of personel responsible for the operational safety of flights should be implemented in aeromedical assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Mental-health effects may be difficult to assess in long COVID patients, and the underlying mechanisms are probably complex; there are data suggesting an association between smoking and sedative use [15] (significant for female gender), a relationship that might not be casual but that rather might reflect anxious behavior. Furthermore, the SARS-CoV-2 epidemic seems to have had an indirect effect on mental health and even somatic symptoms, as was shown in a Greek cohort [80]; similarly, a Turkish transverse study reported that smoking predicted the levels of anxiety experienced by recovered COVID patients who had been hospitalized (OR 4, 95% CI 1.2-12.5) [36], but the authors hypothesize that tobacco use is a coping strategy, rather than a cause. Smoking was found to be associated with sleep disorders, anxiety, and depression in a Chinese cohort that enrolled previously hospitalized COVID-19 patients [39] one year after their discharge, and various mental-health conditions are known to be associated with chronic respiratory diseases [81].…”
Section: Discussionmentioning
confidence: 92%
“…Mental-health effects may be difficult to assess in long COVID patients, and the underlying mechanisms are probably complex; there are data suggesting an association between smoking and sedative use [15] (significant for female gender), a relationship that might not be casual but that rather might reflect anxious behavior. Furthermore, the SARS-CoV-2 epidemic seems to have had an indirect effect on mental health and even somatic symptoms, as was shown in a Greek cohort [80]; similarly, a Turkish transverse study reported that smoking predicted the levels of anxiety experienced by recovered COVID patients who had been hospitalized (OR 4, 95% CI 1.2-12.5) [36], but the authors hypothesize that tobacco use is a coping strategy, rather than a cause. Smoking was found to be associated with sleep disorders, anxiety, and depression in a Chinese cohort that enrolled previously hospitalized COVID-19 patients [39] one year after their discharge, and various mental-health conditions are known to be associated with chronic respiratory diseases [81].…”
Section: Discussionmentioning
confidence: 92%
“…The COVID-19 pandemic has had significant psychological effects on individuals and communities around the world. The fear and uncertainty surrounding the virus [1] as well as the loss of loved ones [2], job insecurities [3], financial hardships [4], reduced sleep quality [5], and forced social isolation caused by lockdown measures [6] have all contributed to mental health challenges for many people.…”
Section: Introductionmentioning
confidence: 99%